Italy's ACE tax and its effect on a firm's leverage - Paolo Panteghini; Maria Laura Parisi; Francesca Pighetti (Center for Economic Studies and ifo Institute (CESifo), 2012)
This article describes the new ACE-type system implemented in Italy since 2012. We have first shown that this system reduces but does not eliminate the financial distortion due to interest deductibility. Using a dataset of Italian companies, we analyzed the impact of this relief on Italian firm capital structure. Despite the permanence of a tax advantage and its gradual implementation, the ACE relief is estimated to reduce significantly leverage. By decreasing default risk it is also expected to reduce systemic risk.
Keywords: H25; H32; 330; ACE; business taxation; leverage; Unternehmensbesteuerung; Eigenkapital; Steuerbegünstigung; Kapitalstruktur; Italien